Seed Scarification Test and ZPT Immersion on Germination of Watermelon Seeds (Citrullus Vulgaris Schard) - Sri Hidayati; Sri Purwanti; Yeni Ika Pratiwi (Agricultural Science, 2019)
Purpose of this study was to determine the effect of the combination of seed scarification treatment and ZPT immersion on the power of watermelon seed germination; to find out the effect of treatment of seed scarification on watermelon seed germination; to find out the effect of ZPT immersion treatment on the power of watermelon seed germination. This experiment was carried out in the laboratory of the Faculty of Agriculture, Merdeka University, Surabaya. Place height of approximately 5 m above sea level. The experiment was arranged factorially in Randomized Block Design (RBD), consisting of two factors: Treatment of seed scarification with 2 levels of treatment and length of immersion of ZPT with 4 treatment levels. Each treatment combination was repeated three times and each combination treatment consisted of 50 seeds watermelon. Factor I is the treatment of seed scarification consisting of without stripping, and stripping Factor II which is the soaking time of ZPT which consists of without soaking; 10 minutes immersion; 20 minutes soaking and 30 minutes soaking. Observations were made every day until the germinated seeds did not germinate again (7 days after germination), observations made included: Germination rate, germination percentage, radicle length, plumula length. The results of statistical analysis showed that the overall combination of seed scarification and soaking of ZPT against watermelon seed germination had not yet given a real interaction effect. Separately the seed scarification treatment had a significant effect on root growth of watermelon sprouts, and did not affect the growth of plumula length, germination percentage and sprout speed, but ZPT immersion treatment significantly affected the percentage of germination, sprout speed, root length growth, and length of plumula growth. . The average percentage of germination, germination rate, length of the plumula and the length of the watermelon seed radicles were best obtained in ZPT immersion treatment with 30 minutes soaking time, which was then followed by other treatments.